A Human Tragedy - Durno, Linda (Refuge: Canada's Journal on Refugees, 1981)
While Canadians were rallying as a nation and individually in response to the plight of the Southeast Asian Boat People, another human tragedy was quietly being played out in the Horn of Africa where Ethiopia and Somalia have been warring over an area known as the Ogaden.